move all values to one side of the equation and solve from there:
x²/2 - x - 1 = 0
x² - 2x - 2 = 0 { Mulitply both sides by 2 }
(2 +/- √(4 + 8)) / 2 { Quadratic formula }
(2 +/- 2√3) / 2 { Simplify }
1 +/- √3
2006-12-04 07:04:42
·
answer #1
·
answered by Dave 6
·
0⤊
0⤋
X^2/2 = x +1
multiply both sides by 2
x^2 = 2x + 2
or x^2 - 2x -2 = 0
using the quadratic formula:
x = -b +/- (sq.root of b^2 - 4 ac) / 2
x = 1 +/- sq. root 3
2006-12-04 15:17:01
·
answer #2
·
answered by Doug R 5
·
0⤊
0⤋
(x^2)/x = x + 1
x^2 = x(x + 1)
x^2 = x^2 + x
0 = x
not possible because x is also a denominator of one side which is not possible because it leaves the number undefined
2006-12-04 15:29:48
·
answer #3
·
answered by trackstarr59 3
·
0⤊
0⤋
1/2 x^2=x+1
x^2=2x+2
x^2-2x-2=0
x=(2+/-â(4+8))/2
x=1+/-1/2 â12
x=1+/-â3
x=1+â3, 1-â3
2006-12-04 15:24:22
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
x^2=2(x+1)
x^2=2x+2
-b+(-)_/(b^2-4ac)
---------------------
2a
x^2-2x-2=0
-(-2)+(-)_/((-2)^2-(4)(1)(-2)
---------------------------------
2(1)
2+(-)_/(4)-(-8)
----------------
2
(2+-_/12)/2
[2+-2_/(3)]/2
(1+-_/3)
2006-12-04 15:08:06
·
answer #5
·
answered by jennytkd13 3
·
0⤊
0⤋